O bom professor na percepção de licenciados em matemática da Unioeste - Wilhelm, Shirley Mara Texeira (2021)
Composing a universal portrait of the “good teacher” is a difficult, if not impossible, task. However, the observation of recurring characteristics in the perception of students about those they consider good teachers, drawn from systematic and rigorous studies related to this topic, can provide clues about the most desirable attributes to be included in this panorama. This dissertation aims to investigate the characteristics of a good teacher in the perception of students from undergraduate courses at the State University of Western Paraná - Unioeste, with attention to courses in the area of Mathematics. The theoretical review of this work was built from the works of important researchers, such as Paulo Freire, Perrenoud, Demo, Tardiff, among others, and seeks to present the teaching principles in search of parameters for the description of a good teacher. Regarding the perception of students about the good teacher, we carried out a survey of data in journal publications collected from the repository of the CAPES journal portal and through Google searches, using a set of previously defined key expressions. The set of selected works was submitted to a thematic analysis, extracting the main objectives and results obtained. For data collection from Unioeste students, a self-administered questionnaire was applied, made available online to students of the Mathematics Licentiate Courses on the Cascavel and Foz do Iguaçu campuses. The questionnaire is composed of open and discursive questions aiming to capture the respondent's spontaneous perception, and multiple-choice questions, aiming to capture perceptions based on stimulated responses. The discursive answers to the open question were analysed using the ideas of Content Analysis and adopting the characteristics associated with the human, technical and ideological dimensions of the pedagogical work as a priori categories. Closed questions value the importance or impact of a certain action or characteristic on the teacher's performance. These valuations were compared with the expressions emerging in the discursive responses. Data analysis suggests a scenario in which students value attributes associated with the human dimension of the teacher's performance, especially the relational characteristics linked to empathy and the ability to communicate effectively with students. In the students' perception, the good teacher has technical mastery of what he teaches, but is not concerned with being a content writer, adopts a healthy dialogue with students and uses teaching strategies in which each subject is involved in the learning process. The teacher is also valued as a social being, who exercises his citizenship and encourages the exercise of citizenship by students, so that teachers in training can grow as people and as professionals.